Complete genome sequence of the endophytic Enterobacter cloacae subsp. Cloacae strain ENHKU01 - Liu, Wing Yee; Chung, K.; Wong, C.; Jiang, J.; Hui, R.; Leung, F. (2012)
Enterobacter cloacae subsp. cloacae strain ENHKU01 is a Gram-negative endophyte isolated from a diseased pepper (Capsicum annuum) plant in Hong Kong. This is the first complete genome sequence report of a plant-endophytic strain of E. cloacae subsp. cloacae.